Church mother : the writings of a Protestant reformer in sixteenth-century Germany - Zell, Katharina, 1497 or 1498-1562 (Other voice in early modern Europe., 2006)
Imbued with character and independence, strength and articulateness, humor and conviction, abundant biblical knowledge and intense compassion, Katharina Schütz Zell (1498?1562) was an outspoken religious reformer in sixteenth-century Germany who campaigned for the right of clergy to marry and the responsibility of lay people?women as well as men?to proclaim the Gospel. As one of the first and most daring models of the pastor?s wife in the Protestant Reformation, Schütz Zell demonstrated that she could be an equal partner in marriage; she was for many years a respected, if unofficial, mother of.